Animal Models of Barrett's Esophagus and Esophageal Adenocarcinoma–Past, Present, and Future. Issue 6 (27th July 2015) - Kapoor, Harit; Lohani, Kush Raj; Lee, Tommy H.; Agrawal, Devendra K.; Mittal, Sumeet K.
Abstract: Esophageal adenocarcinoma is the fastest rising cancer in the United States. It develops from long‐standing gastroesophageal reflux disease which affects >20% of the general population. It carries a very poor prognosis with 5‐year survival <20%. The disease is known to sequentially progress from reflux esophagitis to a metaplastic precursor, Barrett's esophagus and then onto dysplasia and esophageal adenocarcinoma. However, only few patients with reflux develop Barrett's esophagus and only a minority of these turn malignant. The reason for this heterogeneity in clinical progression is unknown. To improve patient management, molecular changes which facilitate disease progression must be identified. Animal models can provide a comprehensive functional and anatomic platform for such a study. Rats and mice have been the most widely studied but disease homology with humans has been questioned. No animal model naturally simulates the inflammation to adenocarcinoma progression as in humans, with all models requiring surgical bypass or destruction of existing antireflux mechanisms. Valuable properties of individual models could be utilized to holistically evaluate disease progression. In this review paper, we critically examined the current animal models of Barrett's esophagus, their differences and homologies with human disease and how they have shaped our current understanding of Barrett's carcinogenesis.